The effectiveness of the rebozo technique and the zilgrei method on labor pain during the active phase I in mothers giving birth - Faidah, Vivin Nur; Purwanti, Heni; Meihartati, Tuti; Sulistyorini, Chandra (Science Midwifery, 2024)
Uncontrolled labor pain causes poor blood circulation to the placenta, resulting in fetal hypoxia and threatening the mother's safety. The hospital has never provided Rebozo technique therapy and the Zilgrei method to mothers in labor. The research analyzed the effectiveness of the Rebozo technique and the Zilgrei method for labor pain in the active phase of the first stage. This type of research is quasi-experimental and Nonequivalent Control Group Design. The population is primigravida mothers giving birth normally from January to September 2023, totaling 385 people with a monthly average of 40 people. The Lameshow formula sample was obtained by 34 people including the intervention and control groups, 17 people each. The results showed that the pain before being given the Rebozo technique was 6 while after being given the Rebozo technique it was 5. The pain before being given the Zilgrei method was 6 while after being given the Zilgrei method it was 5. The Rebozo technique was effective in reducing labor pain in the active phase of the first stage (p value 0.000). The Zilgrei method is effective in reducing pain in the first stage of labor (p value 0.000). There is no difference in the effectiveness of the Rebozo technique and the Zilgrei method for labor pain in the active phase of the first stage (p value 0.985). It can be concluded that the Rebozo and Zilgrei methods can be an alternative to reduce labor pain.